2018
DOI: 10.3892/ol.2018.9400
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated SIRT6 and upregulated NMNAT2 are associated with the presence, depth and stage of colorectal cancer

Abstract: Colorectal cancer (CRC) is an important cause of morbidity and mortality worldwide, and is difficult to detect in its early stages. Diagnostic and prognostic biomarkers are required, which may also be the basis for improving the targeted therapy for CRC. Sirtuin 6 (SIRT6) is a member of the sirtuin family of gene regulators, which have specific functions in genomic stability, gene transcription and energy metabolism in tumorigenesis. Nicotinamide mononucleotide adenylyltransferase 2 (NMNAT2) is a metabolic enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…By contrast, the NMNAT2 gene appears to be amplified in most cancer types (source: www.cbioportal.org) (Cerami et al, 2012). Specifically, NMNAT2 upregulation in colorectal cancer correlates with the invasive depth and TNM stage (Cui et al, 2016;Qi et al, 2018). The upregulated NMNAT2 enzymatic activity in non-small cell lung cancer (NSCLC) can be triggered by SIRT3mediated deacetylation or p53 signaling (Pan et al, 2014).…”
Section: Cytosolic Nad + Poolmentioning
confidence: 99%
“…By contrast, the NMNAT2 gene appears to be amplified in most cancer types (source: www.cbioportal.org) (Cerami et al, 2012). Specifically, NMNAT2 upregulation in colorectal cancer correlates with the invasive depth and TNM stage (Cui et al, 2016;Qi et al, 2018). The upregulated NMNAT2 enzymatic activity in non-small cell lung cancer (NSCLC) can be triggered by SIRT3mediated deacetylation or p53 signaling (Pan et al, 2014).…”
Section: Cytosolic Nad + Poolmentioning
confidence: 99%
“…NMNAT family members catalyze the synthesis of NAD + both in the de novo pathway and the salvage pathway (10,11). Recent studies have shown that NMNAT2 is involved in colorectal cancer progression (12,13). NAPRT is involved in the synthesis of NAD + from nicotinic acid (9).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, downregulation of SIRT6 expression relates to poor prognosis in human colorectal, breast, ovarian, lung, and pancreatic tumors, whereas in other tumors poor outcomes are associated to its overexpression 15,17 . Downregulated SIRT6 and upregulated nicotinamide mononucleotide adenylyltransferase 2 are associated with the presence, depth invasion, stage, and differentiation grade of colorectal cancer (CRC) 18 . SIRT6 phosphorylation by PKCζ at threonine 294 residue mediates fatty acid β-oxidation 19 in human colon cancer cell lines, HCT116 and LoVo cells.…”
mentioning
confidence: 99%